2021
DOI: 10.3389/fpls.2021.663477
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talks Between Macro- and Micronutrient Uptake and Signaling in Plants

Abstract: In nature, land plants as sessile organisms are faced with multiple nutrient stresses that often occur simultaneously in soil. Nitrogen (N), phosphorus (P), sulfur (S), zinc (Zn), and iron (Fe) are five of the essential nutrients that affect plant growth and health. Although these minerals are relatively inaccessible to plants due to their low solubility and relative immobilization, plants have adopted coping mechanisms for survival under multiple nutrient stress conditions. The double interactions between N, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 202 publications
(376 reference statements)
1
39
0
Order By: Relevance
“…In terms of significant relationships among minerals, K had positive correlation with Mn and negative with Zn/On the other hand, B and Cu were inversely related. The first association is in accordance with that mentioned by Fan et al [ 74 ] who reported this relationship among these elements in plants, but for these authors K and Zn had a positive association (whereas B and Cu did not show any relationship). In addition, Na and Mn showed a positive correlation, which would mean that there was a synergism effect between these two elements.…”
Section: Resultssupporting
confidence: 90%
“…In terms of significant relationships among minerals, K had positive correlation with Mn and negative with Zn/On the other hand, B and Cu were inversely related. The first association is in accordance with that mentioned by Fan et al [ 74 ] who reported this relationship among these elements in plants, but for these authors K and Zn had a positive association (whereas B and Cu did not show any relationship). In addition, Na and Mn showed a positive correlation, which would mean that there was a synergism effect between these two elements.…”
Section: Resultssupporting
confidence: 90%
“…The plant ionome is tightly regulated by uptake, translocation, storage, and remobilization as plants aim to maintain their nutrient homeostasis (Courbet et al, 2019). Multiple cross-talks between macro-and micronutrients have been described previously (Fan et al, 2021). The phenomenon of interactions between N and P and also with other nutrients has been recognized, but the underlying mechanisms have not been completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…All these elements interact in a direct and/or indirect manner. In some cases, the deficiency or excess of one element can affect the uptake of other(s), thus conditioning their proper uptake and efficient utilization (Astolfi et al, 2021;Bernal and Kramer, 2021;Pavlovic et al, 2021;Yu et al;Zhou et al). For instance, S deficiency can limit Fe acquisition (Astolfi et al, 2021) while P deficiency can promote it (Figure 1; García et al).…”
Section: Editorial On the Research Topic Nutrient Interactions In Plantsmentioning
confidence: 99%
“…It includes 5 reviews, 1 minireview, 1 perspective and 13 original research articles. Regarding the reviews; one is related to interactions between two essential elements, S and Fe (Astolfi et al, 2021); two are related to interactions between macro-and micro-nutrients (Fan et al, 2021;Kumar et al, 2021); and the other two are dedicated to interactions between beneficial elements, Si and Se, and essential ones (Pavlovic et al, 2021;Zhou et al). The minireview deals with the interaction between N and P in the development of root nodules and cluster roots (Pueyo et al, 2021).…”
Section: Editorial On the Research Topic Nutrient Interactions In Plantsmentioning
confidence: 99%
See 1 more Smart Citation